Model Pendidikan Kepramukaan Indonesia dalam Perspektif Filsafat Pendidikan Paulo Freire - Rusli Akhmad Junaedi (Jurnal Filsafat "WISDOM", 2018)
This research examines the model of Indonesia scouting education by employing Paulo Freire’s perspective on philosophy of education. As an object of analysis, the research discusses the debated on the Regulation of Minister of Education and Culture of the Republic of Indonesia No. 63 of 2014 concerning Scouting Education as a Mandatory Extracurricular in Primary and Secondary Education. The result of this study shows that scouting education in Indonesia is a progressive self-learning process for the youth to fully develop themselves. Paulo Freire’s philosophy of education is a concept of education for liberation. It lays in the premise that the ultimate goal of human existence is the process of humanization. The paper argues that, in general, the character of Indonesian scouting education model is dialogical education which involves intersubjectivity process of education. It becomes de-humanizing education practice when the regulation of scouting education as a mandatory extracurricular activity is enacted. The mandatory regulation forces students’ participation in the scouting education, whereby damaging the volunteerism and freedom dimension of education activities. By doing so, the mandatory regulation distorts the problem-posing education strategy already existing in the Indonesian scouting practices.